SUATU TINDAKAN DALAM PEMBERLAKUAN SUATU UPAYA DALAM ADMINISTRASI PENYELESAIAN SENGKETA SUATU TATA USAHA NEGARA - Indah Putri; indah lestari (Universitas Katolik Widya Karya Malang, 2023)
Administrative efforts are non-litigation settlements that must be taken before state administrative disputes are submitted to the State Administrative Court. It is hoped that the settlement of state administrative disputes as a result of the issuance of a state administrative decision letter is the authority of the State Administrative Court as a judicial body appointed by the Law governing the State Administrative Court. so as to remove the paradigm that the actions of state administrative bodies or officials are always right and cannot be corrected. keywords: Administrative Efforts, State Administrative Court